2016
DOI: 10.1016/j.laa.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Adjacency preservers on invertible hermitian matrices I

Abstract: Hua's fundamental theorem of geometry of hermitian matrices characterizes all bijective maps on the space of all hermitian matrices, which preserve adjacency in both directions. In this and subsequent paper we characterize maps on the set of all invertible hermitian matrices over a finite field, which preserve adjacency in one direction. This and author's previous result are used to obtain two new results related to maps that preserve the `speed of light' on finite Minkowski space-time. In this first paper i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Here the graph is a core, unless we consider 2 ⇥ 2 symmetric matrices in which case the core of a graph is complete. Very recently, the present author showed that the graph, which is formed by invertible hermitian matrices over a field F q 2 with q 2 elements, is a core, provided that q > 4 [13]. In this paper we prove the same result for q = 2.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Here the graph is a core, unless we consider 2 ⇥ 2 symmetric matrices in which case the core of a graph is complete. Very recently, the present author showed that the graph, which is formed by invertible hermitian matrices over a field F q 2 with q 2 elements, is a core, provided that q > 4 [13]. In this paper we prove the same result for q = 2.…”
Section: Introductionsupporting
confidence: 63%
“…Then y j := Q † j x j satisfies y † j y j = 0. By Lemma 13 in case of symmetric matrices, and by [13,Lemma 2.3] applied at 1⇥n matrices y ⇤ 1 , y ⇤ 2 in hermitian case, there is an invertible matrix P such that P † = P 1 and P y 1 = y 2 . If R := (Q 1 2 ) † P Q † 1 , then the automorphism (X) = RXR † satisfies (A 1 ) = A 2 and (B 1 ) = B 2 , so the graph is arc-transitive.…”
Section: Other Properties and A Problem On Hamiltonicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we use HGL n (F q 2 ) also to denote the subgraph in Hn(Fq 2 ), which is induced by the set HGL n (F q 2 ). For q ≥ 4 the next lemma is proved in [15] as a corollary of a more Figure 1. A flower of a rank-one matrix in HGL 2 (F 4 2 ).…”
Section: Since Rk(amentioning
confidence: 94%
“…An example of a such map is ψ(r) := − g(r), 1, 0, g(r) ⊤ , where g : K 4 → K is an injection. Recall that for Theorem 4.10, the non-existence of such maps in finite field case was essentially proven in Lemma 3.8 of the first paper [15], where spectral graph theory and chromatic number of a graph were used.…”
Section: Minkowski Space-timementioning
confidence: 99%